2023
DOI: 10.3390/pathogens12060804
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Biofilm Production Inhibition Activity of Thymus vulgaris L. Essential Oil against Salmonella spp. Isolates from Reptiles

Abstract: Salmonellosis is an infectious disease affecting both animals and humans. Antimicrobial resistant (AMR) and biofilm-producing Salmonella spp., frequently detected in reptiles (who can then act as asymptomatic carriers for warm-blooded animals), have developed resistance to biocides; this represents a warning for the emergence of biocide/antimicrobial cross-resistance. The aim of this study was to evaluate the efficacy of Thymus vulgaris L. essential oil (TEO) in inhibiting bacterial growth and biofilm producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated the strong antibacterial activity of TEO against oral bacteria species [35] and biofilm-producing bacteria [59,60]. Moreover, EOs act with the same effectiveness of NaOCl on antibiotic-sensitive and multidrug-resistant bacteria, even if organized in biofilms [59].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have demonstrated the strong antibacterial activity of TEO against oral bacteria species [35] and biofilm-producing bacteria [59,60]. Moreover, EOs act with the same effectiveness of NaOCl on antibiotic-sensitive and multidrug-resistant bacteria, even if organized in biofilms [59].…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, the utilization of higher concentrations of EOs leads to extensive membrane damage and complete disruption of homeostasis, which ultimately results in the death of cells. Carvacrol and thymol can prevent or interfere with biofilm formation, and they can also eradicate preformed biofilms [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxytyrosol and ampicillin were used as positive controls. The determination of the minimum bactericidal concentration (MBC) was recorded as the lowest extract concentration required to kill bacteria after 24 h of incubation at 37 °C [ 67 ]. Moreover, 100 μL was taken from one well above the MIC value and spread on LB agar plates.…”
Section: Methodsmentioning
confidence: 99%